Risk aversion, patience and intelligence: Evidence based on macro data - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Using the new macro data on risk aversion and patience by Falk et al. (2018), I show that risk aversion and patience are related to intelligence: high-IQ populations are more patient and more risk averse than low-IQ populations. The correlation between patience and intelligence corroborates previous results based on micro data. Intelligent people tend to be patient because they have long time horizons. The correlation between risk aversion and intelligence supports new micro data studies based on dynamically optimized sequential experimentation (Chapman et al. 2018).
Keywords: D00; D81; D90; 330; Risk aversion; patience; intelligence